Análisis fitosociológico de los saladares y manglares de Baja California, México - Delgadillo, Jose; Peinado, Manuel; de la Cruz, Marcelino; Martínez-Parras, José Ma.; Alcaraz, Francisco; de la Torre, Antonio (Instituto de Ecología, A.C., 1992)
A phytosociological study of Baja Californian salt marshes and mangroves is made. The sigmatistic phytosociological approach is used to describe the zonatíon of sixteen recognized  assodations and to define the optimum zone of several  halophilous plants and communities, Ecological, structural and biogeographical data are provided for every assodaiion, and its  syntaxonomical position is discussed.